Design of Microheater for MEMS Based Gas Sensor - Bhatt, Palakkumar (My University, 2014)
We introduce design of micro heater for MEMS based gas sensor for detection various gases in the surrounding environment. MEMS based gas sensors are widely used as they have several advantages like, higher performance, smaller size, ruggedness, low power consumption and low cost. Also metal oxide based sensing surfaces are used with their enormous benefits such as very low cost, high sensitivity, fast response/recovery time, simple electronic interface, ease of use, low maintenance and ability to detect large number of gases. Metal oxide sensor which uses electron depleted surface, either oxidation or reduction process occur on depleted sensing surface (oxide surface) while detection of hazardous gases. In these process electrons are added or extracted depending on metal oxide sensor whether is n-type or p-type. These processes change electrical properties of sensing surface. For oxidation and reduction processes, we need to have high temperature and this can be achieved by placing micro heater below the metal oxide sensing surface. Micro-Heaters have been the subject of great interest owing to their extensive applications in gas sensors, humidity sensors and other micro-systems. A micro-heater should have high temperature to desired level, low power consumption and better temperature uniformity. My work is to geometric optimization of the micro-heater structure to achieve temperature uniformity. Also to compare parameters like, current density distribution, resistance, power consumption and transient temperature response for Poly-Si and Platinum based micro-heater. Different geometries are simulated using COMSOL Multiphysics 4.3 to find out best micro-heater geometry i.e. modified spiral geometry which gives better temperature uniformity. Also effect of voltage variation on temperature and dimensions variation on temperature are simulated and analyzed for Poly-Si and Platinum based micro-heater. After simulations and analysis, conclusion is made by parameters comparison to reach best solution among Poly-Si and Platinum based micro-heaters.
ME, ECED
Keywords: MEMS Gas Sensor